(3GdbjhO GdLeQcjI hJWhQ GdJLGQI GdNGQLjI (B:s (3ddOhd GdBNPI aj Gdfeh(B/ s - (3NdGa YHO GdLGHQ NdGa (B:s; (3QaYJ GdeMLhHs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1975)
(3JHOC GdQSGdI HHGH JegjOj Yf GdSjGSI GdJLGQjI hGdbjhO GdLeQcjI, Ke GdHGH GdChd Yf GdYdGbI GdJLGQjI Hjf GdOhd GdeJbOeI hGdBNPI aj Gdfeh hBKGQgG, hGdHGH GdKGfj Yf SGSGJ GdJNaja ef BKGQ GdbjhO GdLeQcjI, hGdHGH GdKGdK Yf OhQ GdbjhO GdLeQcjI hJWhjQ GdGJLGgGJ GdJLGQjI GdMOjKI(B.s
(3jTJed Ydi edGMb UaMGJ ef (B357 : 368s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1975.s
(3HHdjhLQGajG(B: (3UaMGJ (B369-385.s
Keywords: (3MQjI GdJLGQIs; (3GdSjGSI GdJLGQjIs; (3GdbjhO GdLeQcjIs; (3GdQShe GdLeQcjIs; (3GdbjhO GdJYQjajI GdNGUIs; (3GdbjhO ZjQ GdJYQjajIs; (3GdbjhO GdfbOjIs; (3GdShb GdChQhHjI GdeTJQcIs; (3ejRGf GdeOahYGJs; (3YLR ehGRjf GdeOahYGJs; (3GdeQcR GdJLGQj GdOhdjs; (3GdLGJs; (3SjGSI GdJcJdGJ GdEbdjejIs; (3GJaGbjI dhejs; (3GdJYGhf GdLeQcj GdYQHjs; (3GdShb GdeTJQcI dTQb CaQjbjGs; (3OhQI cfjOjs; (3OhQI Whcjhs; (3GdeRGjG GdLeQcjIs; (3MQjI GdJLGQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1975